2001
DOI: 10.1139/f01-130
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation trajectory of a declining fauna: a century of freshwater mussel fisheries in North America

Abstract: Freshwater mussels (Bivalvia: Unionidae) have been an economically valuable biological resource in North America since the mid-1800s. Although the industries based upon mussel harvest are quite distinct from one another, the trends apparent in harvest statistics are remarkably similar among each successive harvest era. Whether fished for freshwater pearls, button production, or cultured pearl production, market factors have driven commercial harvests while the life history and ecology of mussels have been larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…In general, mussels have experienced a substantial, long-term decline because of historical, commercial exploitation, and periods of poor water quality Theiling 1999, Anthony andDowning 2001). Mussels are strongly affected by local hydrogeomorphic conditions, resulting in "patchy" spatial patterns (Ries et al 2016).…”
Section: Fish Communitymentioning
confidence: 99%
“…In general, mussels have experienced a substantial, long-term decline because of historical, commercial exploitation, and periods of poor water quality Theiling 1999, Anthony andDowning 2001). Mussels are strongly affected by local hydrogeomorphic conditions, resulting in "patchy" spatial patterns (Ries et al 2016).…”
Section: Fish Communitymentioning
confidence: 99%
“…Sub-lethal effects of elevated sediment potentially include reduced immunity to disease, depressed growth rates, and impaired feeding and reproduction [22,23,[25][26][27][28][29][30][31][32][33].…”
Section: Sedimentmentioning
confidence: 99%
“…During this period, commercial musselers harvested untold numbers of unionids for their pearls, which were sold in domestic and international markets. Local populations of mussels were decimated following exhaustive harvesting, after which time the musselers moved on to other, previously untapped, streams (Anthony and Downing, 2001). Overharvest made marketable pearls rarer, and the pearl fishery declined near the end of the century.…”
Section: Commercial Harvestingmentioning
confidence: 99%
“…As plastic buttons began to replace those made from mussel shells in the 1930s and 40s, the rising market of the Japanese cultured pearl industry sparked a new demand for mussel shells. It was found that beads of freshwater mussel shells, when placed inside saltwater pearl oysters, made superior nuclei for the formation of cultured pearls (Anthony and Downing, 2001). This most recent boom has lasted until the mid 1990's, when a combination of declining mussel stocks, increased regulation, foreign competition, and disease outbreaks in Japanese pearl oysters has significantly reduced freshwater mussel harvest in North America (Neves, 1999).…”
Section: Commercial Harvestingmentioning
confidence: 99%